Gender distribution in patients treated with rotablation – analysis of 5, 177 percutaneous coronary interventions based on a large national registry from between 2014 and 2020. (14th October 2021) - Sabatowski, K; Malinowski, K P; Reczuch, K; Dobrzycki, S; Lesiak, M; Hawranek, M; Gil, R J; Witkowski, A; Wojakowski, W; Lekston, A; Gasior, M; Wanha, W; et al.
Abstract: Background: Patients undergoing percutaneous coronary intervention (PCI) procedures using rotational atherectomy (RA) are a special group of patients characterised by the presence of massive calcifications in the coronary arteries. Due to a significant increase regarding the frequency of these procedures in recent years and the distinctiveness of this narrow group of patients among all patients undergoing PCIs, we have characterised the group according to gender. Aims: The aim of analysis was to assess the gender percentage share in following years and differences between both groups of Polish patients undergoing PCI with rotational RA between 2014 and 2020. Methods: Based on the Polish National Registry of Percutaneous Coronary Interventions (ORPKI), we analysed 751, 113 patients treated with PCI between 2014 and 2020. Then, we extracted 5, 177 (0.7%) treated with PCI and RA, 3, 552 of them (68.6%) were males. Selected indices among the two groups were compared using the t-test for continuous variables, the χ 2 test or the likelihood-ratio test for nominal variables where appropriate. To compare means of samples in the following years, one-way ANOVA test was used. Results: The results of the study indicate an upward RA tendency in successive years (p<0.001). Moreover, this tendency and its increase was greater between the years 2016–2019 (Fig. 1). Almost twice as many RA procedures pertain to men, while the percentage share did not undergo a significant change in following years (Fig. 2). The mean age was 72±9 years in the overall group. In the total group, there were 2, 873 patients (55.49%) with chronic coronary syndrome, 1, 033 (19.95%) with unstable angina, 654 (12.63%) with non-ST segment elevation myocardial infarction (NSTEMI) and 494 (9.54%) with ST segment elevation myocardial infarction (STEMI). Females were significantly older in comparison to males [75.2±8.3 vs. 70.5±9.2, p<0.001], more often diabetics [613 (37.72%) vs. 1, 068 (30.07%), p<0.001], less often smokers [173 (10.6%) vs. 635 (17.9%), p<0.001] and were significantly more often treated due to acute coronary syndrome [780 (48.8%) vs. 1, 401 (40.5%), p<0.001]. Considering periprocedural complications among females, there were more cardiac arrests [13 (0.8%) vs. 10 (0.28%), p=0.01] and deaths [11 (0.68%) vs. 6 (0.17%), p=0.006] when compared to males. Conclusion: The percentage of RA among overall PCIs has been still growing in recent years in Poland. The majority of patients treated with RA are men. Gender distribution did not change significantly among patients treated with PCI and RA during the analysed period of time. Funding Acknowledgement: Type of funding sources: None.